Peningkatan Kemampuan Berpikir Kritis Matematis Siswa MTs Melalui Model Problem Based Learning - elza zuria sukmah; Salasiyah, Cut Intan (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2026)
ABSTRACT: This study aims to analyze the effect of applying the Problem Based Learning model on the development of mathematical critical thinking skills in MTs students. The research was conducted with a qualitative approach based on experimentation, using a Pre-Experimental design with the One Group Pretest-Posttest type. The research location was MTs Mon Malem Aceh Besar, with participants consisting of students of class VIII-2 who were randomly selected through random sampling technique. The instruments used were pre-test and post-test questions to measure initial ability as well as changes after the learning intervention.The data analysis process involved the use of Paired Sample Test to identify differences in pre-test and post-test scores, as well as the calculation of N-gain scores as an indicator of the level of improvement in students' critical thinking skills. All data collected from the 15 respondents were thoroughly examined using both methods. The findings from the statistical tests showed that after the implementation of Problem Based Learning, there was a significant increase in students' mathematical critical thinking skills, where the significance value of the hypothesis test was below 0.05, indicating a statistically significant difference. Based on the N-gain score, this increase in critical thinking skills is classified as moderate. Thus, the implementation of the Problem Based Learning model is proven to be effective in improving mathematical critical thinking skills in the school environment, although quantitatively, the level of improvement achieved is only in the moderate category, as shown by the calculation of the N-gain score and the significance of the t-test results ABSTRAK: Penelitian ini bertujuan menganalisis pengaruh penerapan model Problem Based Learning terhadap pengembangan kemampuan berpikir kritis matematis pada siswa MTs. Penelitian dilaksanakan dengan pendekatan kualitatif berbasis eksperimen, menggunakan desain Pre-eksperimental bertipe One Group Pretest-Posttest. Lokasi penelitian adalah MTs Mon Malem Aceh Besar, dengan partisipan yang terdiri atas siswa kelas VIII-2 yang dipilih secara acak melalui teknik random sampling. Instrumen yang digunakan berupa soal pre-test dan post-test untuk mengukur kemampuan awal serta perubahan setelah intervensi pembelajaran. Proses analisis data melibatkan penggunaan Uji-t (Paired Sample Test) untuk mengidentifikasi perbedaan skor pre-test dan post-test, serta perhitungan skor N-gain sebagai indikator tingkat peningkatan kemampuan berpikir kritis siswa. Seluruh data yang dikumpulkan dari 15 orang responden diperiksa secara menyeluruh dengan kedua metode tersebut. Temuan dari uji statistik memperlihatkan bahwa setelah pelaksanaan Problem Based Learning, terdapat peningkatan yang signifikan dalam kemampuan berpikir kritis matematis siswa, dimana nilai signifikansi uji hipotesis berada di bawah 0,05, menandakan adanya perbedaan yang bermakna secara statistika. Berdasarkan skor N-gain, kenaikan kemampuan berpikir kritis ini digolongkan dalam kategori sedang. Dengan demikian, implementasi model Problem Based Learning terbukti efektif dalam meningkatkan kemampuan berpikir kritis matematis di lingkungan sekolah, meskipun secara kuantitatif, tingkat peningkatan yang dicapai hanya berada pada kategori sedang, sebagaimana ditunjukkan oleh hasil perhitungan skor N-gain serta signifikansi hasil uji-t.